Development of contextual teaching-based e-modules in grade v elementary school learning - Mega, Mega Prasrihamni; Marini, Arita; Herlina (Universitas Nusantara PGRI Kediri, 2022)
The purpose of this study was to determine the development of e-modules based on Contextual Teaching in the fifth grade of elementary school learning. This research method uses research and development methods with the ADDIE approach. This research method uses research and development methods with the limits of expert judgment and practicality. Expert assessment is carried out on media, language, and material experts, while practicality with teachers and students. Data collection techniques use documentation and questionnaires, while data analysis techniques use percentages. Based on the results of the study showed that the E- Module Based on Contextual Teaching with an average of 3.70. Thus, it can be concluded that the development of Contextual Teaching-based E-modules in fifth grade elementary school learning is included in the valid or feasible category. From the results of the small group test and large group test, an average of 3.645 was obtained. Thus, it can be concluded that the feasibility of Contextual Teaching-based E-modules in class V elementary school learning is included in the practical or feasible category.